The Burden of Cardiovascular Disease from Air Pollution in Rwanda - Gabriella Taghian; Samantha Fisher; Thomas C. Chiles; Agnes Binagwaho; Philip Landrigan (Ubiquity Press, 2024)
Background: Rwanda, like many countries in sub-Saharan Africa, is still relatively early in development. Industrialization and urbanization are major drivers of the county's economic growth. Rwanda is also undergoing an epidemiological transition, from a pattern of morbidity and mortality dominated by infectious diseases to a pattern shaped by non-communicable diseases (NCDs). The rise in NCDs is due, in part, to increasing exposures to environmental hazards. These include emissions from the growing number of motor vehicles and toxic occupational exposures. Cardiovascular disease (CVD) is now an increasingly important cause of death in Rwanda, and ambient air pollution is a CVD risk factor of growing importance. Objectives: To quantify the burden of CVD attributable to air pollution in Rwanda and identify opportunities for prevention and control of air pollution and pollution-related disease. Methods: We relied on the 2019 Global Burden of Disease (GBD) study for information on levels, sources, and trends in household and ambient air pollution and the burden of pollution-related disease in Rwanda. Information on pollution sources was obtained from the Health Effects Institute State of Global Air 2019 report. Findings: An estimated 3,477 deaths (95% Uncertainty Interval [UI]: 2,500-4,600) in Rwanda in 2019 were attributable to air pollution-related CVD. Of these, 689 (UI: 283-1,300) deaths were from ambient air pollution-related CVD, while 2,788 (UI: 1,800-3,800) deaths were from household air pollution-related CVD. Conclusion: Rwanda is experiencing increased rates of disease and premature death from NCDs, including CVD, as the country grows economically. While household air pollution is still the top pollution-related cause of disease and premature death, rising levels of ambient air pollution are an increasingly important CVD risk factor. Recommendation: Actions taken now to curb rising levels of ambient air pollution will improve health, reduce CVD, increase longevity, and produce great economic benefit for Rwanda. The single most effective intervention against air pollution will be a rapid nationwide transition to renewable energy. We recommend additionally that Rwanda prioritize air pollution prevention and control, establish a robust, nationwide air monitoring network, support research on the health effects of air pollutants, and build national research capacity. The allocation of increased resources for rural and urban public health and health care will complement air pollution control measures and further reduce CVD. To incentivize a rapid transition to renewable energy in Rwanda and other nations, we recommend the creation of a new Global Green Development Fund.